561 Outcome of Patients Undergoing Neck of Femur Fracture Surgery During COVID Period. (4th May 2021) - Saha, A; Demoulin, E; Newman, J
Abstract: Introduction: The aim of the study is to determine the 7- and 30-day mortality rate, hospital stay period and pre- and post-operative symptoms in NOF fracture patients undergoing surgery and compare between COVID-19 positive and negative cohorts. Method: This was a retrospective, descriptive study involving 188 NOF fracture patients who underwent operation from 21/03/20 to 21/07/20 in Mid Yorkshire Hospitals Trust. Only people who tested positive for COVID-19 within 30 days of operation were counted in the positive cohort. Result: Total 21 patient tested positive for COVID-19, 16 within 30 days of operation and 5 tested beyond 30-day period. 24 were not tested. 143 tested negative. The average age of patients was 79.02±11.163 years. Average hospital stay was 14.688±10.657 days (average stay for positive patients 22±13.789 days). 12 patients had pre-operative symptoms (respiratory symptoms, fever) out of which 2(16.67%) tested positive. 7-day post-op mortality was 2.128% (6.25% for COVID-19 positive patients). 30-day mortality was 6.383% (5.814% for untested/negative patients and 12.5% for positive patients). 41 patients (21 .81%) developed post-operative respiratory symptoms (56.25% for positive patients). 8.51% developed post-operative sepsis (25% of positive patients). Conclusions: Mortality and morbidity rate was higher for NOF fracture patients with positive COVID-19 test.